Oral health status of the ethnic group Xukuru from Ororubá: multilevel analysis - Herika de Arruda Mauricio; Rafael da Silveira Moreira (Revista Brasileira de Epidemiologia, 2014)
Objective: To analyse the oral health status of the indigenous people Xukuru from Ororubá aged 10 to 14 years old, in Pernambuco, Brazil. Method: A cross-sectional population-based study developed within the limits of the Indigenous Land Xukuru, from January to March 2010. Oral examinations were performed on a sample of 233 indigenous people. The software SPSS 13.0® was used for descriptive analysis. Later, in order to measure the effect of factors associated with the absence of caries, Poisson log-linear multilevel models were tested with the statistical software MLwiN 2.02®. Results: Oral examinations identified a DMFT Index average of 2.38 (± 2.62). Among all individuals examined, 26.61% were caries free. Multiple regression analysis revealed a negative association between the absence of caries and the variables: higher average of people per household in the villages, higher number of residents per household, older age, male sex, not knowing how to read and write, and very dissatisfied/dissatisfied with teeth/mouth. The variables higher income per capita, not sleeping due to dental problems, had never been to the dentist, no occurrence of toothache, and no need for dental treatment were positively associated with the absence of caries. Conclusion: The absence of caries is associated with contextual and individual factors of the indigenous people Xukuru from Ororubá, aged 10 to 14 years old.